2003
DOI: 10.1111/j.1572-0241.2003.07294.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Patient Survival After Acute Variceal Bleeding: A Multicenter, Cohort Study

Abstract: The mortality rate after variceal bleeding in this study was substantially lower than previously reported. This suggests that advances made in the management of variceal bleeding have improved outcomes after variceal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
3
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(129 citation statements)
references
References 13 publications
9
100
3
17
Order By: Relevance
“…All adverse events occurred during the study period were recorded. Based on the esophageal variceal bleeding rate of 20% in patients treated with beta blockers 3 and 5% in patients receiving EVL plus nadolol, 9 with a two-tailed test to achieve a statistical power of 80% and allowing a type I error of 5%, a sample size of 70 cases in each group were required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All adverse events occurred during the study period were recorded. Based on the esophageal variceal bleeding rate of 20% in patients treated with beta blockers 3 and 5% in patients receiving EVL plus nadolol, 9 with a two-tailed test to achieve a statistical power of 80% and allowing a type I error of 5%, a sample size of 70 cases in each group were required.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopic injection sclerotherapy (EIS) has been a well-established method in the management of acute bleeding from esophageal varices as well as in the prevention of rebleeding. 3 However, EIS is not recommended for prophylaxis of the first episode of variceal hemorrhage because of a possible association with substantial complications. 4 Currently, endoscopic variceal ligation (EVL) has replaced EIS as the endoscopic treatment of choice for management of bleeding esophageal varices.…”
mentioning
confidence: 99%
“…Numerosi trials controllati hanno comparato l'efficacia della TIPS con la terapia medica ed endoscopica nella profilassi del sanguinamento da varici e nel trattamento dell'ascite refrattaria, che rimangono le principali indicazioni, univocamente condivise [1][2][3][4][5][6][7]; le linee guida alla procedura sono state tracciate sulla base di aspetti tecnici angiografici, fattori prognostici clinico-laboratoristici ed incidenza di complicanze. Indicazioni più rare ed oggetto di studi non controllati condotti su piccoli gruppi di pazienti, alcune delle quali non uniformemente accettate sono: la trombosi portale, la sindrome di Budd-Chiari, l'ascite pleurica [8][9][10], la sindrome epato-polmonare (HPS) [11], la sindrome epato-renale (HRS) [3,[12][13][14][15][16][17], la profilassi del sanguinamento intraoperatorio in pazienti cirrotici con ipertensione portale candidati ad interventi di chirurgia addominale maggiore [8,18,19] e la tutela della pervietà portale pre-trapianto epatico (OLT) [20,21].…”
Section: Da Oltre 20 Anni Lo Shunt Intraepatico Porto-sistemico (Tipsunclassified
“…A number of controlled trials have compared the efficacy of TIPS versus medical and endoscopic treatment in preventing variceal bleeding and treating refractory ascites, to date the universally accepted indications for TIPS [1][2][3][4][5][6][7]. Guidelines for the procedure have been established on the basis of technical angiographic aspects, clinical and laboratory prognostic factors and complication rate.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have suggested that the outcome of patients with cirrhosis and acute variceal bleeding has improved over the past two decades. [3][4][5][6][7] However, such improvement could be definitively demonstrated only in a single center study. The aim of the present retrospective study was to evaluate changes in variceal bleeding-related mortality associated with the introduction and combined use of new treatment modalities over the past two decades in a single center.…”
mentioning
confidence: 99%